2012
DOI: 10.1007/s00446-012-0180-x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive throughput in multi-hop wireless networks despite adaptive jamming

Abstract: This article presents a simple local medium access control protocol, called Jade, for multi-hop wireless networks with a single channel that is provably robust against adaptive adversarial jamming. The wireless network is modeled as a unit disk graph on a set of nodes distributed arbitrarily in the plane. In addition to these nodes, there are adversarial jammers that know the protocol and its entire history and that are allowed to jam the wireless channel at any node for an arbitrary (1 − )-fraction of the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Many models have been proposed to depict jamming in wireless networks, including the oblivious jamming mode [30][31][32][33][34][35][36] , in which jamming is initially fixed and unrelated to the particular algorithm execution; the adaptive adversary jamming mode [29,37,38] , in which the adversary can make use of all the history information in a network to online decide the jamming situation in each time step; and the reactive adversary jamming pattern [27,28,39,40] , in which the adversary can not only know the historical information but also use the current network information to make a jamming decision. However, in all of the models mentioned above, jamming is regarded as a uniform binary phenomenon, i.e., all nodes in the network have the same ambient noise, and once the network is jammed, all transmissions in the network fail.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many models have been proposed to depict jamming in wireless networks, including the oblivious jamming mode [30][31][32][33][34][35][36] , in which jamming is initially fixed and unrelated to the particular algorithm execution; the adaptive adversary jamming mode [29,37,38] , in which the adversary can make use of all the history information in a network to online decide the jamming situation in each time step; and the reactive adversary jamming pattern [27,28,39,40] , in which the adversary can not only know the historical information but also use the current network information to make a jamming decision. However, in all of the models mentioned above, jamming is regarded as a uniform binary phenomenon, i.e., all nodes in the network have the same ambient noise, and once the network is jammed, all transmissions in the network fail.…”
Section: Related Workmentioning
confidence: 99%
“…Many jamming models have already been proposed [27][28][29] in the past years, which are based on graph-based and physical interference models. However, all of them regard jamming as a binary phenomenon, which means that when agents are jammed by relatively large ambient noise, they receive nothing.…”
Section: Introductionmentioning
confidence: 99%
“…Our work does not focus on stability, as we assume errors controlled by an unbounded adversary that can always prevent it. The work in [12] considers the problem of devising local access control protocols for wireless networks with a single channel, that are provably robust against adaptive adversarial jamming. At certain time steps, the adversary can jam the communication in the channel in such a way that the wireless nodes do not receive messages (unlike our work, where the receiver might receive a message, but it might contain bit errors).…”
Section: Related Workmentioning
confidence: 99%
“…This throughput metric makes sense for a link without errors or with random errors, where the full capacity of the link can be achieved under certain conditions. However, if adversarial bit errors can occur during the transmission of packets, the full capacity is usually not achievable by any protocol, unless restrictions are imposed on the adversary [2,12]. Moreover, since a bit error renders a whole packet unusable (unless costly techniques like PPR [4] are used), a throughput equal to the capacity minus the bits with errors is not achievable either.…”
mentioning
confidence: 99%
“…In a surprising breakthrough, Awerbuch et al [2] showed that good throughput is possible with a small number of access attempts, even if jamming causes disruption for a constant fraction of the execution. A number of elegant results have followed [37,44,[49][50][51][52][53], with good guarantees on throughput and access attempts.…”
Section: Introductionmentioning
confidence: 99%